Factors Influencing Entrepreneurial Motivation of Undergraduated Students - Rahayu Meliasari; Elly Syahadati; Aunurrahman Aunurrahman; Heti Susanti (Jurnal Pendidikan Bahasa, 2025)
The notion of Edupreneurship course in tertiary institutions has given abundant opportunities for students not only to become entrepreneurs, but also to develop characters for human resources. This study aims to find out the factors affecting entrepreneurial motivation of undergraduated students in English Education Study Program. This research employs descriptive method using direct communication technique. In collecting the data, the researchers used interviews to 30 participants who were officially enrolled in Edupreneurship course. The interview was divided into two aspects: self-concept and entrepreneurship interest. The findings from the results of the interview revealed that the most dominant factor affecting entrepreneurial motivation of students in self-concept is being able to bring happiness to parents with 64%, while in entrepreneurship interest, 30% of the most dominant factor is to be able to get profit.